Factors Influencing Generation Z Customer Loyalty toward 7-Eleven Convenience Stores in the Bangkok Metropolitan Region - Munthongkham, Nattawut; Rouyporn, Arthittaya; Chucheep, Piyaporn (Rajapark Journal, 2026)
This research aimed to compare customer loyalty levels toward 7-Eleven convenience stores among Generation Z consumers across demographic characteristics and to examine the factors influencing customer loyalty toward 7-Eleven convenience stores in the Bangkok Metropolitan Region. Data were collected through questionnaires from 400 respondents and analyzed using descriptive and inferential statistics. The findings revealed that Generation Z consumers of different ages, educational levels, and monthly incomes exhibited varying levels of loyalty toward 7-Eleven convenience stores, whereas no noticeable difference was found with respect to gender. In addition, brand image and brand credibility, as well as employee service, were identified as key factors influencing customer loyalty. In contrast, product variety and service convenience were not found to be major determinants of loyalty among Generation Z consumers. The findings suggest that convenience store operators should place greater emphasis on strengthening brand image and credibility while continuously improving employee service quality to foster customer trust, engagement, and positive service experiences. Such efforts are likely to enhance repeat patronage and strengthen long-term customer loyalty. Furthermore, the results may serve as a useful guideline for developing marketing strategies that are aligned with the behaviors and expectations of Generation Z consumers.